The Participation of Pediatric Dentists in Oral Health Promotion and Education in Serbia - Kilibarda Biljana; Vuković Ana; Marković Evgenija; Perić Tamara; Petrović Bojan; Cakarević Vladimir; Matijević Stevo; Marković Dejan (Sciendo, 2023)
To identify the involvement of Serbian paediatric dentists in oral health promotion and education, and to propose further actions for the improvement of these activities.